2007
DOI: 10.1097/01.olq.0000223287.46097.4b
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenan/MIV-150 (PC-815), a Combination Microbicide

Abstract: Theoretically, PC-815 is likely to be a more efficacious microbicide than Carraguard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 29 publications
3
68
1
1
Order By: Relevance
“…We have previously demonstrated that MIV-150 possesses strong antiviral and potentially virucidal properties, which are not affected by the presence of seminal fluid, and blocks transmission of both R5-and X4-tropic HIV isolates at nanomolar concentrations in vitro (12,50). In our first tests of MIV-150-carrageenan gels, we showed that 500 M MIV-150 in carrageenan was 10 times more active against clinical HIV isolates in vitro than carrageenan alone (12).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…We have previously demonstrated that MIV-150 possesses strong antiviral and potentially virucidal properties, which are not affected by the presence of seminal fluid, and blocks transmission of both R5-and X4-tropic HIV isolates at nanomolar concentrations in vitro (12,50). In our first tests of MIV-150-carrageenan gels, we showed that 500 M MIV-150 in carrageenan was 10 times more active against clinical HIV isolates in vitro than carrageenan alone (12).…”
mentioning
confidence: 80%
“…While Carraguard, a 3% carrageenan gel, was found not to be effective in significantly reducing the number of HIV infections in the treatment arm compared to placebo in a phase 3 clinical trial (45), it was shown to be safe and acceptable by the women who used it in the trial (45) as well as by participants in other studies (27,28,33,35,41,54). Carrageenan-based gels also have favorable rheological properties (12,50), rendering them promising candidates for delivering potent antiviral agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be no effect on sperm motility (84)(85)(86). (85,87). Pre-clinical tests of MIV-150 have shown a significant increase of activity against HIV-1 primary isolates with no toxic effects.…”
Section: A Carageenan Vaginal Gel Formulation For Hiv and Human Papilmentioning
confidence: 99%
“…However, the mechanism of this cell-free inhibition has yet to be determined, and its relevance in vivo is unknown [41]. NNRTI compounds currently in development as microbicides include dapivirine (TMC120), MIV-150, UC 781, and S-DABO [27,42,43].…”
Section: Nonnucleoside Reverse Transcriptase Inhibitorsmentioning
confidence: 99%